2022
DOI: 10.3758/s13423-022-02060-w
|View full text |Cite
|
Sign up to set email alerts
|

Spatial frequency equalization does not prevent spatial–numerical associations

Abstract: There is an intense debate surrounding the origin of spatial–numerical associations (SNAs), according to which small numbers are mapped onto the left side of the space and large numbers onto the right. Despite evidence suggesting that SNAs would emerge as an innate predisposition to map numerical information onto a left-to-right spatially oriented mental representation, alternative accounts have challenged these proposals, maintaining that such a mapping would be the result of a mere spatial frequency (SF) cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Although potentially valid, as the spatial frequency of the adaptor was de facto higher than the spatial frequencies employed for the test, we consider it unlikely for several reasons. On the one hand, behavioral studies demonstrated that the encoding of numerosity information is possible even in case the spatial frequency was kept constant to make it uninformative to solve the task (Adriano et al, 2021(Adriano et al, , 2022 providing evidence for an independence of numerosity encoding to spatial frequency analysis. This result compliments the well-known results about the connectedness effect (He et al, 2009) in which the addition of lines to connect the dots in a display, despite increasing the pattern of high spatial frequency (as more sharp edges are displayed), provides a significant reduction of perceived numerosity to disentangle the two components.…”
Section: Discussionmentioning
confidence: 99%
“…Although potentially valid, as the spatial frequency of the adaptor was de facto higher than the spatial frequencies employed for the test, we consider it unlikely for several reasons. On the one hand, behavioral studies demonstrated that the encoding of numerosity information is possible even in case the spatial frequency was kept constant to make it uninformative to solve the task (Adriano et al, 2021(Adriano et al, , 2022 providing evidence for an independence of numerosity encoding to spatial frequency analysis. This result compliments the well-known results about the connectedness effect (He et al, 2009) in which the addition of lines to connect the dots in a display, despite increasing the pattern of high spatial frequency (as more sharp edges are displayed), provides a significant reduction of perceived numerosity to disentangle the two components.…”
Section: Discussionmentioning
confidence: 99%